Anticancer Effect of Citrus hystrix DC. Leaf Extract and Its Bioactive Constituents Citronellol and, Citronellal on the Triple Negative Breast Cancer MDA-MB-231 Cell Line - Yathsoeung Ho; Nungruthai Suphrom; Krai Daowtak; Pachuen Potup; Yordhathai Thongsri; Kanchana Usuwanthim (MDPI AG, 2020)
Triple negative breast cancer is one of the most aggressive breast cancer type with abilities of early metastasis and chemoresistance. The tropical plant Citrus hystrix DC. has been reported to promote many biological activities including anticancer. However, the effect of C. hystrix against triple negative breast cancer has not yet been identified. This study aimed to evaluate the anticancer properties of C. hystrix leaf extract and its bioactive constituents citronellol and citronellal against the triple negative breast cancer MDA-MB-231 cell line. C. hystrix leaves were powdered and sequentially macerated. The in vitro anticancer effects of C. hystrix leaf extracts, and its bioactive constituents (citronellol and citronellal) were evaluated against MDA-MB-231 cell line using cytotoxic MTT assay, cell proliferation, wound scratch migration, colony formation, cell cycle, apoptosis assay, Hoechst staining, RT-qPCR, and Western blot analysis. Results showed that crude hexane extract, citronellol, and citronellal significantly reduced cell proliferation, colony formation, and cell migration by inducing cell cycle arrest, while also inducing apoptosis in MDA-MB-231 cells through inhibition of anti-apoptotic Bcl-2 expression, leading to activation of the caspase-3-dependent pathway. This study is the first report to demonstrate the effect of C. hystrix, citronellol, and citronellal against triple negative breast cancer MDA-MB-231 cells.